Gender Bias and Perceptions of the Nursing Profession in Croatia: A Cross-Sectional Study Comparing Patients and the General Population - Marijana Neuberg PhD; Danijela Sopić MSc; Tina Košanski MSc; Mateja Križaj Grabant MSc; Rosana Ribić PhD; Tomislav Meštrović MD, PhD, MPH (SAGE Publishing, 2024)
Background The way the nursing profession is perceived plays a pivotal role in shaping the public's attitude toward its members, primarily influenced by interactions with nurses and media representation. However, it can be significantly impacted by historical and traditional stereotypes, coupled with enduring gender bias and other preconceived notions. Objectives The study aimed to examined how the title "nurse" reflects the profession's identity, perception as a female occupation, and status as a healthcare activity. It also assessed awareness of nurses' roles, education and public presence, comparing general population and patients' opinions in the Republic of Croatia. Methods Conducted as a cross-sectional study, this research employed a structured questionnaire and a convenience sampling approach. It encompassed both the general population and patients from Croatia, with data collection spanning from February 15, 2023, to March 16, 2023, and resulting in a total sample size of 624 participants. Statistical analysis included both descriptive and inferential techniques, and significance was set at p  < .01 (two-tailed). Results A substantial proportion of respondents, amounting to 38.1%, correlate the term "nurse" with the role of the physician's assistant, whereas only 49.5% associate it with a true professional functioning within their field of work. Furthermore, 73.7% study participants perceive the nursing profession as being desirable for men. Upon examining the perspectives of the general population and patients, statistically significant differences emerged in terms of their perceptions regarding the perceived work scope ( p  < .001) and the level of sufficient educational attainment ( p  < .001) of nursing professionals. Conclusion The analysis uncovers varying perceptions of the nursing profession in the Republic of Croatia, as well as evolving perceptions of gender diversity within nursing roles. Differing viewpoints between the general population and patients in this study emphasize the need for tailored education and communication initiatives to improve the image of nursing.